Evaluating the effectiveness of a self‐management exercise intervention on wound healing, functional ability and health‐related quality of life outcomes in adults with venous leg ulcers: a randomised controlled trial. Issue 1 (27th January 2016) - O'Brien, Jane; Finlayson, Kathleen; Kerr, Graham; Edwards, Helen
Abstract: Exercise that targets ankle joint mobility may lead to improvement in calf muscle pump function and subsequent healing. The objectives of this research were to assess the impact of an exercise intervention in addition to routine evidence‐based care on the healing rates, functional ability and health‐related quality of life for adults with venous leg ulcers (VLUs). This study included 63 patients with VLUs. Patients were randomised to receive either a 12‐week exercise intervention with a telephone coaching component or usual care plus telephone calls at the same timepoints. The primary outcome evaluated the effectiveness of the intervention in relation to wound healing. The secondary outcomes evaluated physical activity, functional ability and health‐related quality of life measures between groups at the end of the 12 weeks. A per protocol analysis complemented the effectiveness (intention‐to‐treat) analysis to highlight the importance of adherence to an exercise intervention. Intention‐to‐treat analyses for the primary outcome showed 77% of those in the intervention group healed by 12 weeks compared to 53% of those in the usual care group. Although this difference was not statistically significant due to a smaller than expected sample size, a 24% difference in healing rates could be considered clinically significant. The per protocol analysis for wound healing, however, showed that those in the intervention group who adhered to the exercise protocol 75% or more of the time were significantly more likely to heal and showed higher rates for wound healing than the control group ( P = 0·01), that is, 95% of those who adhered in the intervention group healed in 12 weeks. The secondary outcomes of physical activity, functional ability and health‐related quality of life were not significantly altered by the intervention. Among the secondary outcomes (physical activity, functional ability and health‐related quality of life), intention‐to‐treat analyses did not support the effectiveness of the intervention. However, per protocol analyses revealed encouraging results with those participants who adhered more than 75% of the time ( n = 19) showing significantly improved Range of Ankle Motion from the self‐management exercise programme ( P = 0·045). This study has shown that those participants who adhere to the exercise programme as an adjunctive treatment to standard care are more likely to heal and have better functional outcomes than those who do not adhere to the exercises in conjunction with usual care.